Psychosocial Stressors among Generalized Anxiety Disorder Patients in a Tertiary Level Hospital of Bangladesh - Hossain, Md Jahangir; Das, Chayon Kumar (Journal of Monno Medical College, 2022)
Background: Psychosocial stressors are the most common perpetuating factors of the Generalized Anxiety Disorder (GAD) patients in Psychiatry outpatient departments. Objectives: The objective is to identify the psychosocial stressors among GAD patients visiting a tertiary level hospital. Methods: A cross-sectional study was conducted from June 2019 to December 2020, involving 227 individuals aged above 18 years and residing in Manikganj. Patients visiting Psychiatry outdoor department of the tertiary level hospital (Monno Medical College and Hospital, Gilondo, Manikganj) were taken as study subjects. Psychiatric diagnosis was confirmed by consultant Psychiatrist following standard definition. A semi-structured questionnaire was used to collect socio-demographic information and psychosocial stressors. Ethical issues were maintained throughout the study. Results: Our analysis shows a strong association between psychosocial factors and GAD as majority of the patients had at least one of the psychosocial stressors involved. During considering psychosocial factors, it was seen that higher number of the respondents mentioned to have financial crisis (154, 67.8%) and familial disharmony (109, 48%). Other factors (75, 33.0%) such as Covid-19 infection, effect of lockdown, home isolation had also contributed as psychosocial factors. Family member in the abroad were found among 67 (29.5%) and disease related anxiety among 57 (25.1%) of the respondents. Contraceptive use (45, 19.8%) was found as another contributing factor during the study period. Conclusions: Most of the patients with GAD have association with psychosocial stressors in this particular demographic region. Hormonal contraceptive use in female patients was an atypical finding- hence this study shows need of the larger research in this area and it points the association of psychosocial stressors among GAD patients. J Monno Med Coll June 2022;8(1): 6-9